PENGARUH PENGGUNAAN MEDIA VISUAL TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 5-6 TAHUN DI TK ISLAM UMMI KAMALIYAH KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Widya Safitri; Daviq Chairilsyah; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of field observation on the ability to recognize the concept of the number of students has not developed optimally. So it is necessary to apply the use of visual media. This study aims to determine the effect of the use of visual media on the ability to recognize the concept of the number of children aged 5-6 years in TKIslam Ummi Kamaliyah Bangko district of Rokan Hilir district. The sample used in this study were 18 students. The data collection techniques used are observation and documentation. Data analysis technique used t-test with SPSS 20.0. Research hypothesis is the activity of the use of visual media has an influence to the ability to recognize the concept of the number of children aged 5-6 years in kindergarten Islam Ummi Kamaliyah. This can be known from the analysis of data obtained thitung = 17,517 and Sig. (2-tailed) = 0.000. Because Sig. (2-tailed) = 0.000 <0,05 it can be concluded that there is a difference in the ability to recognize the concept of significant number of students after the use of visual media in learning. The hypothesis test can be seen thitung= 17,517 > t tabel= 2,110. So it means Ho is rejected and Ha accepted which means there is a very significant difference between before and after doing experiments by applying the use of visual media. The influence of the use of visual media on the ability to recognize the concept of the number of children aged 5-6 years in TK Islam Ummi Kamaliyah Bangko district of Rokan Hilir district of 61,96%.Keywords: Ability to Know the Concept of Numbers, Use of visual media